Effectiveness of self-managed abortion during the COVID-19 pandemic: Results from a pooled analysis of two prospective, observational cohort studies in Nigeria - Ijeoma Egwuatu; Sybil Nmezi; Ruvani Jayaweera; Relebohile Motana; Belén Grosso; Ika Ayu Kristianingrum; Ruth Zurbriggen; Chiara Bercu; Caitlin Gerdts; Heidi Moseson (Public Library of Science (PLoS), 2022)
Globally, restrictions imposed by the COVID-19 pandemic altered access to clinical abortion care, as well as people's ability to access abortion medications on their own. When clinical care is inaccessible, or when self-care is preferred, people use pills on their own, without clinical supervision, to end their pregnancies-a practice known as "self-managed" abortion. Little is known about experiences of self-managed abortion during the COVID-19 pandemic. The aim of this study was to measure experiences of self-managed abortion, including abortion completion, prior to and during the COVID-19 pandemic in Nigeria. Between October 2019-September 2020, we recruited callers to a safe abortion accompaniment group that provides information on self-managed abortion in Nigeria. Participants completed a baseline phone survey, and two follow-up phone surveys. Primary outcomes included burdens experienced prior to versus during the pandemic, and abortion completion. We calculated frequencies and percentages overall and by time period and compared outcomes across time periods using t-tests, Chi-squared tests, tests of proportion, and Mantel-Haenszel adjusted odds ratios. Overall, 807 participants were included in these analyses. Participants enrolled during the COVID-19 pandemic were more likely to report needing to borrow money (47.9% vs 29.4%) and find lodging outside the home (15.5% vs 3.2%) for their self-managed abortion than were those enrolled prior to the pandemic. Participants reported COVID-19 related difficulties most frequently during the earliest and strictest period of the lockdowns, particularly in obtaining and taking pills (32.4%), and comfort seeking healthcare (12.2%). Nearly all participants (95%) reported a complete abortion at last follow-up. Results from this study underscore the challenges Nigerians faced during the COVID-19 pandemic in self-managing their abortions, and also the essential role that a safe abortion hotline played in expanding access to safe abortion during a time when the formal healthcare system was less accessible and higher-risk.